Knowledge sharing among medical teachers: the interplay between personality and the theory of planned behavior - Hatam Faraji Dehsorkhi; Ali Asghar Hayat (BMC Medical Education)
Abstract Introduction Knowledge sharing is critical to the quality of medical education and healthcare services. However, medical teachers encounter multiple barriers, such as content dispersion and a lack of shared knowledge management. Using structural equation modeling (SEM), this study aimed to (1) assess the predictive power of the Theory of Planned Behavior (TPB) in explaining knowledge-sharing intention and behavior among medical teachers and (2) examine the moderating effect of the Big Five personality traits on the relationship between knowledge-sharing intention and behavior. Methods This cross-sectional correlational study involved a sample of 237 medical teachers from Shiraz University of Medical Sciences, Iran, who completed two validated and reliable questionnaires: a researcher-developed TPB questionnaire and a personality questionnaire developed by Rammstedt and John (2007). Data were collected in 2024 and analyzed using partial least squares structural equation modeling (PLS-SEM). Results Structural equation modeling analysis, conducted using SmartPLS 3, revealed that knowledge-sharing intention was significantly influenced by perceived behavioral control (β = 0.37, p < 0.001), attitude (β = 0.24, p < 0.001), and subjective norms (β = 0.28, p < 0.001). Additionally, knowledge-sharing behavior was significantly predicted by knowledge-sharing intention (β = 0.20, p < 0.001) and perceived behavioral control (β = 0.12, p < 0.01). Among the Big Five personality traits, only conscientiousness significantly moderated the knowledge-sharing intention–behavior relationship (β = 0.41, p < 0.001). Conclusion By integrating the Five-Factor Model of personality into TPB, this study demonstrated that TPB is a suitable framework for predicting knowledge-sharing behavior among medical teachers. Furthermore, it revealed that personality traits, particularly conscientiousness, may mediate the relationship between knowledge-sharing intention and behavior. These findings have practical implications for medical administrators in designing effective systems and interventions to enhance knowledge sharing among academics.